Junie B., first grader : aloha-ha-ha! - Park, Barbara; Brunkus, Denise (New York : Random House, 2006)
Excitable Junie B. Jones manages to find trouble both before and during a trip to Hawaii and records each incident in a photo journal given to her by her teacher.
"A Stepping Stone book."
2.6
K-3.
K-3
Keywords: Diaries -- Juvenile fiction; Jones, Junie B. (Fictitious character) -- Juvenile fiction; Photojournalism -- Juvenile fiction; Schools -- Juvenile fiction; Vacations -- Juvenile fiction; Diaries -- Fiction; Jones, Junie B. (Fictitious character) -- Fiction; Photojournalism -- Fiction; Schools -- Fiction; Vacations -- Fiction; Diaries -- Fiction; Jones, Junie B. (Fictional character) -- Fiction; Photojournalism -- Fiction; School stories; Vacations -- Fiction; Hawaii -- Juvenile fiction; Hawaii -- Fiction; Hawaii -- Fiction; Diary fiction